Prefunctionalized Porous Organic Polymers: Effective Supports of Surface Palladium Nanoparticles for the Enhancement of Catalytic Performances in Dehalogenation. Issue 35 (28th July 2016) - Zhong, Hong; Liu, Caiping; Zhou, Hanghui; Wang, Yangxin; Wang, Ruihu
Abstract: Three porous organic polymers (POPs) containing H, COOMe, and COO − groups at 2, 6‐bis(1, 2, 3‐triazol‐4‐yl)pyridyl (BTP) units (i.e., POP‐1, POP‐2, and POP‐3, respectively) were prepared for the immobilization of metal nanoparticles (NPs). The ultrafine palladium NPs are uniformly encapsulated in the interior pores of POP‐1, whereas uniform‐ and dual‐distributed palladium NPs are located on the external surface of POP‐2 and POP‐3, respectively. The presence of carboxylate groups not only endows POP‐3 an outstanding dispersibility in H2 O/EtOH, but also enables the palladium NPs at the surface to show the highest catalytic activity, stability, and recyclability in dehalogenation reactions of chlorobenzene at 25 °C. The palladium NPs on the external surface are effectively stabilized by the functionalized POPs containing BTP units and carboxylate groups, which provides a new insight for highly efficient catalytic systems based on surface metal NPs of porous materials. Abstract : POP out : The introduction of carboxylate groups not only endows porous organic polymers (POPs) a superior dispersibility in H2 O/EtOH, but also results in the variation of the size and location of palladium nanoparticles (NPs) from the interior pores to the external surface (see figure). Surface palladium NPs show a superior catalytic activity, stability, and recyclability in the dehalogenation of aryl halides.